Electrizarte: combining engineering education, arts and social outreach in an extra-curricular activity - Willink Castro, Teodoro (2015)
In the Electrical Engineering undergraduate program of the University of Costa Rica, most of the design and analysis projects are guided, structured and related to a specific topic, limiting technical content and machining the way problems are solved, which in turn, restricts the motivated student creativity. The ElectrizArte Project provides the opportunity to develop both technical and not-technical skills in a extra-curricular enviroment. As the main theme, ElectrizArte allows students to design, implement, and operate projects that combine engineering with art, taking advantage of the particular situation that many of the students participating in the project, have interest in art in general, or practice some artistic activity.